Modeling and optimization of ISFET microsensor for the use of quality testing in food and pharmaceutical industry - Yeo, Tiong Chia (2021)
Ion-sensitive field-effect transistor (ISFET) is one of the most promising chemical sensors that has many advantages such as high integration capability, low cost, simple interface, and high productivity. ISFET has the capability to detect various molecules such as enzymes, antibodies and proteins, but pH sensing is mainly discussed in this paper. An ISFET model is developed using the TCAD tool - COMSOL Multiphysics 5.5 to study the characteristics of the ISFET as a pH sensor. The model also used to investigate the effects of gate insulator materials, other geometry consideration and operating condition on ISFET performance. The Id-Vg characteristics, threshold voltage, electric potential, and sensitivity of the ISFET were analysed. The simulated results were verified against approximated values calculated using the surface potential equation. It was observed that the tantalum pentoxide, Ta2O5 dielectric material has the highest sensitivity, which is very near to the calculated Nernst limit and thinner oxide layer can result in smaller threshold voltage which may lead to lower the power consumption. © 2021 IEEE.